EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) PADA SISWA KELAS VII.5 SMP NEGERI 3 PALLANGGA - Evi Novianty (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
This study is an experimental study that aims to determine the effectiveness cooperative learning model type of the Teams Games Tournament (TGT) in learning mathematics in class VII.5 students of SMP Negeri 3 Pallangga, Gowa Regency. The research design used was a one group pretest-posttest design and carried out for 6 meetings. Data collection techniques used were learning outcomes tests given to students, student activity observation sheets and teacher's ability to manage learning and student response questionnaires. The results of the descriptive analysis show that: (1) the average score of students' mathematics learning outcomes is 84.90 and is in the high category with a standard deviation of 10.89 where the lowest score obtained is 55 and the highest score is 100.00 from the ideal score of 100; (2) the average frequency of student activities in learning activities has increased; (3) student response questionnaires showed that 82.66% of students gave positive responses to TGT cooperative learning; (4). Based on the results of the study, the cooperative learning model of the Teams Games Tournament (TGT) type is effectively applied in learning mathematics in class VII students of SMP Negeri 3 Pallangga, Gowa Regency. Keywords : Efektivitas, Experimental, dan Teams Games Tournament